Processing Criteria and Experimental Data Quality for a High Compression Ratio Spark Ignition Engine (2016)
This article presents the evaluation of some of these methodologies applied to a high compression ratio-spark ignition engine, which was achieved through modification of a commercial Diesel engine. The accuracy on calculation of equivalence ratio from exhaust gas analysis and the start of combustion from mass fraction burned has been tested. The effect of trapped mass on the in-cylinder energy balance was determined. The results suggest that the tested methodologies for calculation of equivalence ratio, start of combustion, and trapped are reliable tools for evaluation of quality of data and studying spark ignition engines with high compression ratios.